2020
DOI: 10.1177/0273475320939261
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Student Perceptions of Academic Program Quality and Relationships to Surface, Deep, and Strategic Learning Approaches

Abstract: A substantial body of empirical research outside of the marketing education literature indicates that students adopt surface, deep, or strategic learning approaches based on their learning environment, among other factors. Using the Revised Approaches to Studying Inventory and the Course Experience Questionnaire, this exploratory research examines upper-level marketing majors’ learning approaches, their perceptions of the overall academic quality of their program of study, and the relationships between those t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 71 publications
(172 reference statements)
1
11
0
Order By: Relevance
“…Rather, it could be concluded that, given the specifics of primary research mentioned, emphasis should be placed on certain other variables contained in the same framework. In this sense, one can consider including the already mentioned personality factors in future research (Wedel, Thomsen & Larsen, 2015;Humburg, 2017;Wild & Alvarez, 2020), the theory of planned behavior (Chipidza, Green & Riemenschneider, 2019;Moore & Burrus, 2019), the quality of the study program of the program (Faranda, Clarke & Clarke, 2021). Additionally, their inclusion makes sense having in mind the lack of specific research that connects the mentioned variables and the study program in Digital Marketing.…”
Section: Research Results Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, it could be concluded that, given the specifics of primary research mentioned, emphasis should be placed on certain other variables contained in the same framework. In this sense, one can consider including the already mentioned personality factors in future research (Wedel, Thomsen & Larsen, 2015;Humburg, 2017;Wild & Alvarez, 2020), the theory of planned behavior (Chipidza, Green & Riemenschneider, 2019;Moore & Burrus, 2019), the quality of the study program of the program (Faranda, Clarke & Clarke, 2021). Additionally, their inclusion makes sense having in mind the lack of specific research that connects the mentioned variables and the study program in Digital Marketing.…”
Section: Research Results Discussionmentioning
confidence: 99%
“…It should be noted that, in addition to the above determinants, personality factors (Vedel, Thomsen & Larsen, 2015;Humburg, 2017;Wild & Alvarez, 2020), relevant theories, such as the theory of planned behavior, may be included in the research of study program selection, (Chipidza, Green & Riemenschneider, 2019;Moore & Burrus, 2019), and the quality of the program itself (Faranda, Clarke & Clarke, 2021).…”
Section: H2mentioning
confidence: 99%
“…More attention has also been drawn to the process and essential conditions when explicating deep learning, for example, the learner's identity and connection with the world (Fullan et al, 2019 ), or learners' motivation and teachers' scaffolding roles (Tochon, 2013 ). Inspired by “twenty-first-century skills,” the twenty-first century has witnessed the results-oriented research of deep learning, which emphasizes the cultivation of learners' critical thinking and problem-solving ability, creativity and innovation, and communication and cooperation (Asikainen, 2014 ; Esteban-Guitart and Gee, 2020 ; Faranda et al, 2021 ). It is He and Li ( 2005 ) who first introduced the concept of deep learning to the education domain in China.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, deep learning has attracted great attention in the field of higher education ( Chotitham et al, 2014 ), and high imagination and creativity, emphasizing cooperation, coordination, integration, interpretation, personalization, and learning to learn will be the major requirement for individuals to satisfy the needs of talents of social development ( Esteban-Guitart and Gee, 2020 ), thus higher education should cultivate students to satisfy the requirement of social development. Deep learning emphasizes the in-depth participation of students in the learning process, broader understanding of knowledge, achieving intrinsic interest and ability, seeking meaning between content, connecting ideas with previous knowledge and daily experience, understanding all presenting materials, participating in the content of the course, collaborating with others, using evidence to test logic, and the various advanced abilities which meet the requirements of higher education for the development of students’ ability ( Asikainen, 2014 ; Faranda et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%